Pengaruh Media Pembelajaran Menggunakan Media Video MateriBanjir Dan Kebencanaan Terhadap Hasil Belajar Siswa Kelas VIIDi SMPN 03 Colomadu, Kabupaten Karanganyar - Rizka Hidayat, Chairul; , Drs. Dahroni M.Si (2016)
SMPN 03 Colomadu addressed in Jalan Adisumarmo Airport Colomadu subdistrict, Karanganyar, Central Java province and telephone number (0271) 781135. Learning media used in the classroom is very influential on student learning outcomes. This study using video media to test whether or not the media influence learning using video media, in accordance with the purpose of learning. This study uses two classes as a population that is class VII G and class VII H. classes as the experimental class VII G and class VII H as the control class. Determination of control class and experimental class views of the average value of the pre-test students, classes that get the highest score as the control class, while the class who received the lowest average value into the experimental class. Control class in learning are not using video media but still uses a strategy TGT (Team Games Tournamen), while the control class using video media and strategy TGT. Mechanical testing instrument using validity, reliability testing and data retrieval assessed learning outcomes of students increased by the calculation about the pre-test and post-test. Data were analyzed using normality test, homogeneity test, and test all hypotheses using SPSS 17. The data obtained show that control class scored an average of 73.75 while the experimental group scored an average of 84.37. Pre-test and post-test control group scored significantly (two-tailed) is greater than the probability value of 0.100> 0.05 H0, while the control group scored significantly lower than the probability value 0.000 <0.05, H0 rejected and Ha accepted. The conclusion obtained the effect of improving student learning outcomes using instructional media using video media content and the flood disaster in class VII SMPN 03 Colomadu, Karanganyar.